Hardening accelerator for hydraulic materials, cement composition, and hardened body

By using specific proportions of hardening material accelerators for calcium formate, inorganic calcium compounds and sulfate, the problem of degradation of the fluidity of the hardened material is solved, and a more efficient hardening process and initial strength development is achieved, and production efficiency is improved.

JP7628149B2Active Publication Date: 2025-02-07DENKA CO LTD

Patent Information

Application Number
JP2023052210
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-28
Publication Date
2025-02-07
Estimated Expiration
2043-03-28

AI Technical Summary

Technical Problem

In the prior art, the fluidity of the hardened material used rapidly decreases after mixing with water, resulting in the subsequent compaction work taking time and energy and reducing production efficiency.

Method used

A hardening material accelerator containing 20.0% to 80.0% calcium formate, 15.0% to 70.0% inorganic calcium compounds and 0.5% to 30.0% calcium sulfate-free sulfate is used, and 4.5% to 65.0% calcium sulfa aluminate is used to improve the fluidity maintenance and initial strength development of the hardened material.

Benefits of technology

It effectively improves the fluidity maintenance and initial strength development of hardened materials, reduces hardening time, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628149000001
    Figure 0007628149000001
  • Figure 0007628149000002
    Figure 0007628149000002
  • Figure 0007628149000003
    Figure 0007628149000003
Patent Text Reader

Abstract

To provide a curing accelerator for a hydraulic material, capable of improving the fluidity retention, coagulation property, and initial strength development of a hydraulic material.SOLUTION: The curing accelerator for the hydraulic material contains calcium formate in an amount of 20.0 to 80.0 mass%, an inorganic calcium compound in an amount of 15.0 to 70.0 mass% and an inorganic sulfate excluding calcium sulfate in an amount of 0.5 to 30.0 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hardening accelerator for hydraulic materials, and a cement composition and a hardened product containing said accelerator. [Background technology]

[0002] Hydraulic materials such as cement used in the civil engineering and architectural fields are usually mixed with water and left to harden for a certain period of time. The hardening speed of hydraulic materials can be affected by the ratio of the materials to water, the surrounding environmental temperature, and the curing method, but the time it takes for hydraulic materials to harden can be shortened by using an admixture that accelerates hardening, i.e., a hardening accelerator.

[0003] Reducing the time it takes for hydraulic materials to harden leads to improved productivity at work sites. For example, concrete hardened bodies used in precast construction methods for reinforced concrete buildings and the like can generally be obtained by casting a cement composition into a formwork, leaving it to stand for a predetermined time, and then curing it by steam curing or the like, but the use of a hardening accelerator can reduce the time it takes for the concrete to reach an initial strength that allows it to be demolded, allowing the hardened bodies to be produced efficiently.

[0004] In addition, after pouring the cement composition, it is usually "compacted" using a vibrator or the like to distribute the cement composition evenly within the formwork. However, if the fluidity of the cement composition has decreased immediately after pouring, the compaction requires a lot of effort and time, resulting in reduced productivity.

[0005] Regarding hardening accelerators, for example, Patent Document 1 discloses a hardening accelerator for hydraulic materials that contains a predetermined amount of inorganic sulfate, calcium sulfoaluminate, and inorganic hydroxide. Patent Document 2 discloses a hardening accelerator for hydraulic materials that has a Blaine specific surface area of ​​4000 cm 2 The document discloses a cement admixture containing calcium sulfoaluminate having a calcium sulphoaluminate content of 1000 mg / g or more and one or more salts selected from the group consisting of formates, acetates and lactates. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2014-19618 A [Patent Document 2] JP 2010-235399 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, hydraulic materials using hardening accelerators such as those described above lose their fluidity immediately after mixing with water, and compaction after pouring requires effort and time, which raises concerns about reduced productivity.

[0008] In view of the above, an object of the present invention is to provide a hardening accelerator for hydraulic materials that can improve the fluidity retention, setting property, and early strength development of the hydraulic material. [Means for solving the problem]

[0009] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that the problems can be solved by a hardening accelerator for hydraulic materials containing calcium formate, an inorganic calcium compound, and an inorganic sulfate other than calcium sulfate in a specified ratio, and have arrived at the present invention. That is, the present invention is as follows.

[0010] [1] A hardening accelerator for hydraulic materials, comprising 20.0 to 80.0 mass% calcium formate, 15.0 to 70.0 mass% inorganic calcium compound, and 0.5 to 30.0 mass% inorganic sulfate other than calcium sulfate. [2] The hardening accelerator for hydraulic materials according to the above [1], wherein the inorganic calcium compound is at least one selected from the group consisting of calcium sulfate, calcium hydroxide, calcium carbonate, and calcium oxide. [3] The hardening accelerator for hydraulic materials according to [1] or [2] above, wherein the inorganic sulfate is at least one selected from the group consisting of sulfate, thiosulfate, sulfite, bisulfite, pyrosulfate, and pyrobisulfite. [4] The hardening accelerator for hydraulic materials according to any one of the above [1] to [3], further comprising 4.5 to 65.0 mass % of calcium sulfoaluminate. [5] A cement composition comprising the hardening accelerator for hydraulic materials according to any one of the above [1] to [4] and cement. [6] The cement composition according to the above [5], wherein the content of the hardening accelerator for hydraulic materials is 0.5 to 10 mass %. [7] A hardened body obtained by hardening the cement composition described in [5] or [6] above. [8] A method for producing a hardened body, comprising hardening a cement composition containing the hardening accelerator for hydraulic materials according to any one of the above [1] to [4], cement, and water by steam curing at a maximum temperature of 40 to 80°C for 2 to 8 hours. Effect of the Invention

[0011] According to the present invention, it is possible to provide a hardening accelerator for hydraulic materials that can improve the fluidity retention, setting property, and early strength development of the hydraulic material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, one embodiment of the present invention (the present embodiment) will be described in detail, but the present invention is not limited to this embodiment. In the present invention, the term "hydraulic material" refers to a material that hardens when kneaded with water, and the term "hardened body" refers to hardened cement paste, mortar, concrete, etc. In addition, "%" and "parts" in this specification are based on mass unless otherwise specified.

[0013] [Curing accelerator for hydraulic materials] The hydraulic material hardening accelerator according to the present embodiment contains 20.0 to 80.0 mass% calcium formate, 15.0 to 70.0 mass% inorganic calcium compound, and 0.5 to 30.0 mass% inorganic sulfates other than calcium sulfate. The hydraulic material hardening accelerator not only accelerates the hardening of the hydraulic material when the hydraulic material is kneaded with water and hardens, but may also harden itself while accelerating the hardening.

[0014] (Calcium Formate) The hardening accelerator for hydraulic materials contains calcium formate at 20.0 to 80.0 mass%, preferably 30.0 to 70.0 mass%, and more preferably 40.0 to 65.0 mass%. If the calcium formate content is less than 20.0 mass%, the fluidity retention, setting property, and early strength development of the hydraulic material may not be improved, and if it exceeds 80.0 mass%, the fluidity retention, setting property, and early strength development may not be improved.

[0015] (Inorganic calcium compounds) The hardening accelerator for hydraulic materials contains an inorganic calcium compound in an amount of 15.0 to 70.0% by mass, preferably 18.0 to 60.0% by mass, and more preferably 20.0 to 40.0% by mass. If the content of the inorganic calcium compound is less than 15.0% by mass, the fluidity retention, setting property, and early strength development of the hydraulic material may not be improved, and if it exceeds 70.0% by mass, the fluidity retention, setting property, and early strength development of the hydraulic material may not be improved.

[0016] In this embodiment, the inorganic calcium compound is preferably one or more selected from the group consisting of calcium sulfate, calcium hydroxide, calcium carbonate, and calcium oxide. When two or more inorganic calcium compounds are used, the total of the respective contents is the content of the inorganic calcium compounds. In this embodiment, from the viewpoint of early strength development, it is preferable to use calcium sulfate, calcium hydroxide, and / or calcium oxide, and calcium sulfate is more preferable. When calcium sulfate is used, it is more preferable that it is anhydrous.

[0017] (Inorganic Sulfates) The hardening accelerator for hydraulic material contains 0.5 to 30.0 mass %, preferably 1.0 to 25.0 mass %, more preferably 3.0 to 15.0 mass % of inorganic sulfates other than calcium sulfate. If the content of inorganic sulfates other than calcium sulfate is outside the range of 0.5 to 30.0 mass %, the fluidity retention, setting property, and early strength development of the hydraulic material may not be improved.

[0018] In this embodiment, the inorganic sulfate is preferably one or more selected from the group consisting of sulfate, thiosulfate, sulfite, bisulfite, pyrosulfate, and pyrobisulfite. When two or more inorganic sulfates are used, the total of the respective content ratios is the content ratio of the inorganic sulfate. As inorganic substances that form salts, alkali metals and alkaline earth metals are preferred. In this embodiment, from the viewpoint of early strength development, it is preferred to use sulfate and / or thiosulfate, sodium sulfate, aluminum sulfate, sodium thiosulfate, and potassium alum are more preferred, and from the viewpoint of early strength development, sodium sulfate and aluminum sulfate are even more preferred, and among them, sodium sulfate is even more preferred from the viewpoint of improving fluidity retention. When sodium sulfate is used, it is more preferred to use anhydrous sodium sulfate.

[0019] The hardening accelerator for hydraulic material according to the present embodiment further contains calcium sulfoaluminate in an amount of preferably 4.5 to 65.0 mass%, more preferably 15.0 to 60.0 mass%, and even more preferably 30.0 to 50.0 mass%. When the content of calcium sulfoaluminate is within the above range, the fluidity retention and early strength development of the hydraulic material can be improved. Calcium sulfoaluminate is a general term for hydraulic substances and hydrated salts represented by the chemical formula xCaO·yAl2O3·zCaSO4·mH2O (x, y, and z are non-zero positive real numbers, and m is 0 or a positive real number). Examples include auyn (3CaO·3Al2O3·CaSO4), AFt phase represented by ettringite (3CaO·Al2O3·3CaSO4·32H2O), AFm phase represented by monosulfate (3CaO·Al2O3·CaSO4·12H2O), and those in which AFt and AFm phases coexist. Calcium sulfoaluminate may be amorphous. In addition, a part of Al2O3 may be replaced by a small amount of Fe2O3 or SiO2, and a part of CaSO4 may be replaced by Ca(OH)2 or CaCO3. In the present invention, z cannot be set to 0 in the above chemical formula xCaO yAl2O3 zCaSO4 mH2O, because then the hydraulic material would not be able to maintain its fluidity and there is a risk of a decrease in strength during hardening due to a phase transition.

[0020] Calcium sulfoaluminate can be produced by blending raw materials such as lime and other calcia raw materials, gypsum and other sulfate raw materials, and bauxite (aluminum hydroxide) and other alumina raw materials in a predetermined ratio, for example, a molar ratio of CaO:CaSO4:Al2O3 of 3:3:1, firing at about 1,500°C using a kiln or the like, and pulverizing. Alternatively, silicon dioxide or the like may be added to the fired material, which is then heat-treated and pulverized.

[0021] The Blaine specific surface area value (hereinafter simply referred to as the "Blaine value") of calcium sulfoaluminate is 1,000 to 6,000 cm 2 / g, and 2,000 to 4,000 cm 2 / g, and more preferably 2,200 to 3,800 cm 2 It is more preferable that the molecular weight is / g. In the present invention, the Blaine specific surface area value is measured in accordance with the specific surface area test described in JIS R 5201:2015 "Physical Testing Methods for Cement".

[0022] [Cement composition] The cement composition according to the present embodiment contains a hardening accelerator for hydraulic materials and cement.

[0023] The cement is not particularly limited, and examples thereof include various Portland cements such as ordinary, early strength, super early strength, low heat and medium heat, various mixed cements obtained by mixing blast furnace slag, fly ash, silica fume, etc. with these Portland cements, environmentally friendly cements (eco-cement) manufactured using municipal waste incineration ash and sewage sludge incineration ash as raw materials, commercially available fine particle cements, white cements, etc., and various cements can be used in a fine powder form. In addition, cements adjusted by increasing or decreasing the amount of components (e.g., gypsum, etc.) normally used in cements can also be used. Furthermore, a combination of two or more of these can also be used. From the viewpoint of increasing the early strength development, it is preferable to select ordinary Portland cement or early strength Portland cement, but early demolding is possible even when blast furnace cement or fly ash cement with low early strength development is used.

[0024] The cement used in the present invention has a Blaine specific surface area of ​​2,500 cm from the viewpoints of production cost and strength development. 2 / g~7,000cm 2 / g, and 2,750 cm 2 / g~6,000cm 2 / g, and more preferably 3,000 cm 2 / g~4,500cm 2 It is more preferable that the molecular weight is / g.

[0025] The content of the hydraulic material hardening accelerator in the cement composition is preferably 0.5 to 10 mass%, more preferably 1.0 to 9.0 mass%, and further preferably 2.5 to 8.0 mass%. When the content of the hydraulic material hardening accelerator in the cement composition is within the above range, the fluidity retention, setting property, and early strength development of the hydraulic material can be improved.

[0026] The flow value of the cement composition before pouring is preferably 160 to 230, more preferably 170 to 220, and even more preferably 190 to 200. When the flow value of the cement composition is within the above range, pouring and compaction are easily performed, and workability is improved. Furthermore, the rate of change in the flow value one hour after kneading the cement composition (flow change rate) is preferably less than 20%, more preferably less than 15%, and even more preferably less than 10%. When the flow change rate of the cement composition is within the above range, pouring and compaction are easily performed, and workability is improved, even if pouring is performed one hour after kneading the cement composition. In the present invention, the flow value can be measured in accordance with the method specified in JIS R 5201:2015 "Physical Testing Methods for Cement." The rate of change in flow can be calculated by subtracting the value calculated by (flow value after 1 hour of mixing) / (flow value immediately after mixing)×100(%) from 100%.

[0027] The cement composition preferably contains aggregate. As the aggregate to be used, the same fine aggregate or coarse aggregate as that used in ordinary cement mortar or concrete can be used. That is, river sand, river gravel, mountain sand, mountain gravel, crushed stone, crushed sand, limestone aggregate, lime sand, silica sand, colored sand, artificial aggregate, blast furnace slag aggregate, sea sand, sea gravel, artificial lightweight aggregate, heavy aggregate, etc. can be used, and these can also be combined.

[0028] The content of the aggregate is preferably 40 parts by mass or more and 250 parts by mass or less, more preferably 50 parts by mass or more and 230 parts by mass or less, and even more preferably 60 parts by mass or more and 200 parts by mass or less, relative to 100 parts by mass of cement in the cement composition. By having the content of the aggregate within the above range, the fluidity retention and early strength development of the hydraulic material can be improved.

[0029] The cement composition may contain an alkali metal carbonate. By containing an alkali metal carbonate, the cement composition is likely to have good fluidity retention and early strength development. Examples of the alkali metal carbonate include sodium carbonate, potassium carbonate, lithium carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, and lithium hydrogen carbonate, and these may be combined.

[0030] The content of the alkali metal carbonate is preferably 1 to 6 parts by mass, more preferably 2 to 5 parts by mass, in terms of the solid content relative to 100 parts by mass of cement in the cement composition. When the content of the alkali metal carbonate is within the above range, it is easy to improve the fluidity retention and early strength development.

[0031] The cement composition may contain a siliceous fine powder. The siliceous fine powder contained in the cement composition can improve fluidity retention and early strength development. Examples of the siliceous fine powder include latent hydraulic substances such as granulated blast furnace slag powder, fly ash, and pozzolanic substances such as silica fume, among which silica fume is preferred. The type of silica fume is not limited, but from the viewpoint of fluidity, it is more preferred to use silica fume containing 10% or less of ZrO2 as an impurity or acidic silica fume. Acidic silica fume refers to silica fume that exhibits an acidity of pH 5.0 or less when 1 g of silica fume is added to 100 cc of pure water and stirred.

[0032] The fineness of the silica powder is not particularly limited, but usually, the fine powder of granulated blast furnace slag and fly ash has a Blaine value of 3,000 cm2 / g or more 9,000cm 2 / g or less, and silica fume has a BET specific surface area of ​​20,000 cm 2 / g or more 300,000cm 2 / g or less.

[0033] The content of the siliceous fine powder is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and even more preferably 3 to 12 parts by mass, relative to 100 parts by mass of cement in the cement composition. When the content of the siliceous fine powder is equal to or more than the lower limit, the fluidity retention and early strength development are easily improved. Furthermore, when the content of the siliceous fine powder is equal to or less than the upper limit, the fluidity retention is easily improved.

[0034] The cement composition may contain an antifoaming agent to the extent that it does not adversely affect the performance. The antifoaming agent is used for the purpose of suppressing the amount of air entrained during mixing. The type of antifoaming agent is not particularly limited as long as it does not significantly adversely affect the strength properties of the hardened mortar, and either liquid or powder form may be used. For example, polyether-based antifoaming agents, polyhydric alcohol-based antifoaming agents such as esters of polyhydric alcohols and alkyl ethers, alkyl phosphate-based antifoaming agents, silicone-based antifoaming agents, etc. may be mentioned.

[0035] The content of the antifoaming agent is preferably 0.002 to 0.5 parts by mass, more preferably 0.005 to 0.45 parts by mass, and even more preferably 0.01 to 0.4 parts by mass, relative to 100 parts by mass of cement in the cement composition. When the content of the antifoaming agent is equal to or more than the lower limit, the antifoaming effect can be sufficiently exhibited, and when the content of the antifoaming agent is equal to or less than the upper limit, the fluidity retention can be easily improved.

[0036] In addition, the cement composition may contain one or more of the following admixtures, provided that they do not adversely affect performance: gas foaming substances, water reducing agents, air entraining agents, rust inhibitors, water repellents, antibacterial agents, colorants, antifreeze agents, fine limestone powder, finely cooled blast furnace slag powder, sewage sludge incineration ash and its molten slag, urban waste incineration ash and its molten slag, and pulp sludge incineration ash; thickeners; shrinkage reducing agents; polymers; clay minerals, such as bentonite and sepiolite; and anion exchangers, such as hydrotalcite.

[0037] [Cured body] The hardened body according to the present embodiment is obtained by hardening the cement composition. The hardened body is usually formed by kneading the cement composition with water, and the cement, which is a hydraulic material, undergoes a hydration reaction and hardens. The amount of water for mixing is not particularly limited, but is preferably 10 to 70 parts by mass, more preferably 14 to 65 parts by mass, and even more preferably 16 to 60 parts by mass, relative to 100 parts by mass of the cement composition. When the amount of water for mixing is within the above range, it is easy to improve the initial strength development of the hydraulic material.

[0038] The hardened body is obtained by kneading the cement composition with water and then leaving it to harden, but it can also be obtained more efficiently by filling (casting) the mixture into a formwork and curing it, or by pouring it directly into the application area, or by spraying or painting it.

[0039] The compressive strength of the hardened concrete depends on the type of cement used, but is 10.5 to 15.0 N / mm 6 hours after casting. 2 It is preferable that the resistance is 11.0 to 14.0 N / mm 2 More preferably, the resistance is 12.0 to 13.0 N / mm 2 It is more preferable that the material has a strength of 40.0 to 50.0 N / mm 2 It is preferable that the strength is 41.0 to 48.0 N / mm 2 More preferably, the resistance is 42.0 to 46.0 N / mm 2 It is even more preferable that: In the present invention, the compressive strength can be measured in accordance with the method specified in JIS R 5201:2015 "Physical Testing Methods for Cement".

[0040] [Method of manufacturing the hardened body] The method for producing a hardened body according to this embodiment is a method for hardening a cement composition containing a hardening accelerator for hydraulic materials, cement, and water by steam curing for 2 to 8 hours at a maximum temperature of 40 to 80° C. The method for producing a hardened body preferably includes, in this order, a kneading step of kneading the hardening accelerator for hydraulic materials, cement, and water, a casting step of filling a formwork with the mixed cement composition, and a curing step of curing the cement composition filled in the formwork.

[0041] The mixing method in the mixing step is not particularly limited, and each material may be mixed at the time of construction, or some or all of the materials may be mixed in advance. As a mixer, any existing device such as a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, a Plosser mixer, or a Nauta mixer can be used.

[0042] The casting method in the casting step can be a known method. The temperature of the cement composition during casting is preferably 0 to 50° C., more preferably 10 to 40° C. When the temperature of the cement composition during casting is within the above range, the hardened body can be easily demolded early.

[0043] The method for producing the hardened body preferably further includes a compaction step after the casting step. The compaction method may be a known method, but from the viewpoint of workability, it is preferable to use a vibrator. The cement composition containing the hardening accelerator for hydraulic materials of the present invention has good fluidity just before casting, so that compaction can be easily performed, the cement composition can be uniformly distributed in the formwork, and air bubbles mixed in during casting can be removed.

[0044] As a curing method used in the curing step, from the viewpoint of improving productivity, it is preferable to use steam curing using a curing chamber or a heating sheet. Steam curing is usually performed by raising the temperature of the atmosphere around the target and maintaining a constant temperature while maintaining a moderate humidity. The conditions of steam curing are preferably a maximum temperature of 40 to 80°C and a curing time of 2 to 8 hours, more preferably a maximum temperature of 40 to 75°C and a curing time of 2.5 to 7.5 hours, and even more preferably a maximum temperature of 45 to 60°C and a curing time of 3 to 7 hours. If the maximum temperature of the atmosphere around the cement composition during steam curing is set within the above range and the curing time is set within the above range, it becomes easier to enable early demolding of the hardened body.

[0045] The relative humidity around the cement composition during steam curing is preferably 50% RH or more, more preferably 75% RH or more, and even more preferably 90% RH or more. There is no upper limit, but it may be 100% RH. When the relative humidity around the cement composition during steam curing is within the above range, it becomes easier to quickly demold the hardened body.

[0046] The curing step preferably includes a pre-curing step. The pre-curing conditions are preferably a temperature of 10 to 50°C, and the temperature is kept constant for about 1 to 3 hours. By including the pre-curing step in the curing step, the temperature inside the poured cement composition can be made uniform, and thermal cracks due to the temperature difference between the inside and outside can be easily prevented.

[0047] The curing step preferably includes a heating step. A known method can be used as the heating method, and the temperature is preferably increased at a rate of 10 to 30° C. / hour, more preferably at a rate of 12 to 28° C. / hour, and even more preferably at a rate of 15 to 25° C. When the temperature increase rate in the heating step is within the above range, hardening can be further promoted while preventing thermal cracking due to a sudden increase in temperature of the cement composition.

[0048] The curing step preferably includes a temperature holding step. As the temperature holding method, a known method can be used, and a constant temperature is preferably held at a temperature range of 40 to 80°C for 1 to 8 hours, more preferably at a temperature range of 40 to 75°C for 1 to 6 hours, and even more preferably at a temperature range of 45 to 65°C for 2.5 to 5 hours. By holding a constant temperature within the above numerical range in the temperature holding step, the poured cement composition can be hardened uniformly, and early demolding can be easily achieved.

[0049] The method for producing a hardened body preferably includes a natural cooling step after the curing step. In the natural cooling step, the hardened body obtained by the curing step is naturally cooled in a room temperature atmosphere. The cooling time is not particularly limited, but it is sufficient that the hardened body is cooled to a temperature at which it can be easily demolded, and may be about 0.5 to 2 hours. By including the natural cooling step after the curing step, it is possible to prevent thermal cracking of the hardened body. EXAMPLES

[0050] The present invention will be further described below based on experimental examples, but the present invention is not limited to these.

[0051] <Experimental Example 1> Using the following materials, mortar with a water / cement ratio of 45% and a cement to aggregate ratio of 1:2.5 (mass ratio) was prepared. A water reducer was added to the obtained mortar in the ratio shown in Table 1, and the mixture amount of a hydraulic material hardening accelerator with the composition shown in Table 1 was kneaded to obtain the ratio shown in Table 1, to prepare a cement composition. The flow value of the obtained cement composition was measured, and the flow change rate was calculated. The initial time was also measured. Both are shown in Table 1. The prepared cement composition was filled into a form measuring 4 x 4 x 16 cm, and then steam cured to obtain a hardened body. The steam curing conditions were 1 hour pre-curing at 20°C, 1.5 hours of temperature increase at a rate of 20°C / hour, 3 hours of temperature retention at 50°C, and 0.5 hours of natural cooling. The compressive strength of the hardened body was measured. The results are shown in Table 1.

[0052] (Materials used) Cement: Ordinary Portland cement (commercially available), Blaine specific surface area 3,200 cm 2 / g, specific gravity 3.15g / cm 3 Water: Tap water Aggregate: River sand from the Himekawa River system in Niigata Prefecture Water reducing agent: Polycarboxylic acid-based high-performance water reducing agent (commercially available) Calcium formate: Reagent Calcium sulfate (inorganic calcium compound): Reagent Sodium sulfate (inorganic sulfate): anhydrous, reagent

[0053] (Measurement items) Flow change rate: According to the method specified in JIS R 5201:2015 "Physical test method for cement", the flow value of the cement composition was measured immediately after mixing and one hour after mixing. The flow values ​​immediately after mixing were all about 200. Using each measured flow value, the flow change rate was calculated as (flow change rate) = 1 - (flow value one hour after mixing) / (immediately after mixing) × 100. Initial setting time: Complies with the method specified in JIS A 1147:2019 "Test method for setting time of concrete", and the penetration resistance is 3.5N / mm 2 The time when this occurs was set as the starting time. Compressive strength: In accordance with the method specified in JIS R 5201:2015 "Physical testing methods for cement," the compressive strength of the hardened body 6 hours after the end of steam curing (immediately after demolding) and 7 days after the end of steam curing was measured.

[0054] [Table 1]

[0055] From the results shown in Table 1, it was confirmed that by using a hardening accelerator for hydraulic materials containing calcium formate, inorganic calcium compounds, and inorganic sulfates other than calcium sulfate in a specified ratio, the fluidity retention, setting properties, and early strength development of the cement composition can be improved.

[0056] <Experimental Example 2> Mortar, cement composition, and hardened body were prepared and the flow rate, initial time, and compressive strength were measured in the same manner as in Experimental Example 1, except that calcium hydroxide, calcium carbonate, and calcium oxide were used as inorganic calcium compounds in the hardening accelerator for hydraulic materials in the ratios shown in Table 2 in addition to calcium sulfate. The results are shown in Table 2.

[0057] (Inorganic calcium compounds) Calcium hydroxide: Reagent Calcium carbonate: Reagent Calcium oxide: Reagent

[0058] [Table 2]

[0059] From the results shown in Table 2, it was confirmed that the fluidity retention, setting property, and early strength development of the cement composition can be improved by using calcium sulfate, calcium hydroxide, calcium carbonate, and calcium oxide as the inorganic calcium compound contained in the hardening accelerator for hydraulic materials. In particular, it was confirmed that the early strength development of the cement composition can be improved when calcium sulfate is contained.

[0060] <Experimental Example 3> Mortar, cement composition, and hardened body were prepared and the flow rate, initial time, and compressive strength were measured in the same manner as in Experimental Example 1, except that aluminum sulfate, potassium alum, and sodium thiosulfate were used as inorganic sulfates in the hardening accelerator for hydraulic materials in the ratios shown in Table 3. The results are shown in Table 3.

[0061] (Inorganic Sulfates) Aluminum sulfate: Reagent Potassium alum: Reagent Sodium thiosulfate: Reagent

[0062] [Table 3]

[0063] From the results shown in Table 3, it was confirmed that the fluidity retention, setting property, and early strength development of the cement composition can be improved by using sodium sulfate, aluminum sulfate, potassium alum, and sodium thiosulfate as inorganic sulfates contained in the hardening accelerator for hydraulic materials. Among them, it was confirmed that when sodium sulfate and aluminum sulfate are contained, the early strength development can be further improved, and in particular, when sodium sulfate is contained, the fluidity retention can be further improved.

[0064] <Experimental Example 4> Mortar, cement composition, and hardened body were prepared and the flow rate, initial time, and compressive strength were measured in the same manner as in Experimental Example 1, except that calcium sulfoaluminate was further added to the hardening accelerator for hydraulic materials in the proportions shown in Table 4. The results are also shown in Table 4.

[0065] (Calcium Sulfoaluminate) First-grade reagent calcium carbonate, calcium sulfate dihydrate, and aluminum hydroxide were mixed so that the molar ratio of CaO:CaSO4:Al2O3 was 4:3:1, and the mixture was fired at 1,400°C for 2 hours and allowed to cool to room temperature to produce a mixture with a Blaine specific surface area of ​​3,500 cm. 2 A sample product was ground to / g.

[0066] [Table 4]

[0067] From the results shown in Table 4, it was confirmed that when the hardening accelerator for hydraulic materials further contains calcium sulfoaluminate, the early strength development can be improved.

[0068] <Experimental Example 5> Mortar, cement composition, and hardened body were prepared and the flow rate, initial time, and compressive strength were measured in the same manner as in Experimental Example 1, except that the mixing amount of the hardening accelerator for hydraulic materials was set to the ratio shown in Table 5. The results are also shown in Table 5.

[0069] [Table 5]

[0070] From the results shown in Table 5, it was confirmed that by adjusting the mixing amount of the hydraulic material hardening accelerator within a specified range, the fluidity retention, setting property, and early strength development of the cement composition can be improved.

[0071] <Experimental Example 6> Except for using blast furnace cement and fly ash cement as the cement composition, mortar, cement composition, and hardened body were prepared in the same manner as in Experimental Example 1, and the flow rate, initial time, and compressive strength were measured. The results are shown in Table 6.

[0072] (cement) Blast furnace cement type B: Commercial product, Blaine specific surface area 3,200 cm 2 / g, specific gravity 3.15g / cm 3 Blast furnace type C cement: Commercially available, Blaine specific surface area 3,500 cm 2 / g, specific gravity 3.15g / cm 3 Fly ash cement type B: Commercially available product, Blaine specific surface area 3,200 cm 2 / g, specific gravity 3.15g / cm 3

[0073] [Table 6]

[0074] From the results shown in Table 6, it was confirmed that even when blast furnace cement or fly ash cement is used as the cement in the cement composition, the fluidity retention, setting property, and early strength development of the cement composition can be improved.

[0075] From the above results, it has been confirmed that the hardening accelerator for hydraulic materials of the present invention contains calcium formate, an inorganic calcium compound, and an inorganic sulfate in a predetermined ratio, and thereby can improve the fluidity retention, setting property, and early strength development of the cement composition. [Industrial Applicability]

[0076] The hardening accelerator for hydraulic materials of the present invention contains calcium formate, an inorganic calcium compound, and an inorganic sulfate other than calcium sulfate in a predetermined ratio, and thereby can improve the fluidity retention, setting property, and early strength development of hydraulic materials. Therefore, the hardening accelerator can be widely applied to the fields of civil engineering and construction, such as hardened concrete bodies used in precast construction methods.

Claims

1. The composition contains 24.0 to 80.0 mass% calcium formate, 15.0 to 70.0 mass% inorganic calcium compound, and 0.5 to 20.0 mass% inorganic sulfate other than calcium sulfate, The inorganic calcium compound is at least one selected from the group consisting of calcium sulfate, calcium hydroxide, calcium carbonate, and calcium oxide, The hardening accelerator for hydraulic materials, wherein the inorganic sulfate is at least one selected from the group consisting of sulfates, thiosulfates, sulfites, bisulfites, pyrosulfates, and pyrobisulfites.

2. The hardening accelerator for hydraulic materials according to claim 1, further comprising 4.5 to 65.0 mass % of calcium sulfoaluminate.

3. A method for producing a hydraulic material comprising the hardening accelerator according to claim 1 or 2 and cement, The content of the hydraulic material hardening accelerator is 0.5 to 10 mass %.

4. A hardened body obtained by hardening the cement composition according to claim 3.

5. A method for producing a hardened product, comprising: hardening a cement composition containing the hardening accelerator for hydraulic materials according to claim 1 and cement by steam curing at a maximum temperature of 40 to 80°C for 2 to 8 hours.

Citation Information

Patent Citations

  • Grouting material for fabricated structure

    CN108503309A

  • Manufacture of concrete product

    JP1999090918A

  • Hardening accelerator and cement composition

    JP2003277111A

  • Cement admixture and cement composition

    JP2010235399A

  • Curing accelerator for hydraulic material, hydraulic composition, method for manufacturing hydraulically cured object, and hydraulically cured object

    JP2014019618A

Cited By

  • Concrete composition, hardened body, and method for producing hardened body

    JP2026046776A